The Breakthrough Listen Search for Intelligent Life: No Evidence of Claimed Periodic Spectral Modulations in High-resolution Optical Spectra of Nearby Stars. (4th December 2018) - Isaacson, Howard; Siemion, Andrew P. V.; Marcy, Geoffrey W.; Hickish, Jack; Price, Danny C.; Enriquez, J. Emilio; Gizani, Nectaria
Abstract: We report on high-resolution spectra obtained by the Automated Planet Finder and high-resolution optical Levy Spectrometer to search for periodic spectral modulations, such as those reported in Borra & Trottier. In their analysis of 2.5 million spectra from the Sloan Digital Sky Survey, Borra & Trottier report periodic spectral modulations in 234 stars, and suggest that these signals may be evidence of extraterrestrial civilizations. To evaluate this claim, we observed three of the 234 stars with the Automated Planet Finder Telescope and Levy Spectrometer including all stars brighter than a visual magnitude of 14. Fourier analysis of the resultant spectra of these three sources does not reveal any periodic spectral modulations at the reported period, nor at any other period.